Bacteriostatic activities of N-substituted tris-thioureas bearing amino acid and aniline substituents - Wan Sharifatun Handayani, Wan Zullkiplee; Maya Asyikin, Mohd Ariff; Hasnain, Hussain; Wan Mohd Khairul; Zainab Ngaini (Taylor and Francis Ltd., 2016)
A series of tri-substituted thiourea derivatives were synthesized by the reaction of 1,3,5-triacetylbenzoyl isothiocyanate with aminoacids and aniline derivatives. All thiourea derivatives were characterized by FT-IR, 1H and 13C NMR spectroscopy. Antibacterial activities against wild-type Escherichia coli American Type Culture Collection 8739 were determined by use of the turbidimetric methodto evaluate the effect of varying amino groups on the synthesized thioureas. Tris-thiourea derivatives bearing ortho-chloroaryl substituents showed excellent antibacterial activity against E. coli with minimal inhibitory concentration (MIC) of 96 ppm. The optimum inhibition was dependent on the type of amines and the position of the halogen in aniline.